Challenges are no barrier for Muhammad Adhwa in earning his degree - Naqiah, Puaad (UMPSA, 2024)
GAMBANG, 27 October 2024 – Muhammad Adhwa Mohd Salemi, 24, has proven that his disability is not an obstacle to his success as he received his degree at the 19th Convocation Ceremony of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA).